2023
DOI: 10.3390/ijerph20032126
|View full text |Cite
|
Sign up to set email alerts
|

Civic Engagement and Personality: Associations with the Big Five and the Dark Triad

Abstract: Several studies have analyzed the relationship between general personality traits and attitudes and behaviors, indicating that a person is more committed to the community. After raising the question of whether malevolent traits might also be related, the aim was to analyze the relationship between civic engagement and personality, delving into the contribution of the Dark Triad (narcissism, Machiavellianism, and psychopathy) and controlling for the association with the Big Five. The Civic Engagement Questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…In fact, future research could explore the associations between IH, civic engagement, and narcissism, given that R/S leaders may be susceptible to narcissism and the finding that greater IH corresponded to an indicator of greater vulnerable narcissism (Jankowski et al, 2019). In addition, Rico-Bordera et al (2023) found a positive association between civic engagement and grandiose narcissism, suggesting a self-enhancement motive rather than the other-oriented motivation for activism.…”
Section: Limitations and Future Directionsmentioning
confidence: 94%
“…In fact, future research could explore the associations between IH, civic engagement, and narcissism, given that R/S leaders may be susceptible to narcissism and the finding that greater IH corresponded to an indicator of greater vulnerable narcissism (Jankowski et al, 2019). In addition, Rico-Bordera et al (2023) found a positive association between civic engagement and grandiose narcissism, suggesting a self-enhancement motive rather than the other-oriented motivation for activism.…”
Section: Limitations and Future Directionsmentioning
confidence: 94%